Analisis Faktor-Faktor yang Memengaruhi Efektivitas Sistem Informasi Akuntansi pada PT. Sinar Niaga Sejahtera Jember - Akbar Dwi Setiawan; Muhammad Firdaus; Nurshadrina Kartika Sari (JAKUMA : Jurnal Akuntansi dan Manajemen Keuangan, 2024)
This study aims to analyze the effect of personal ability, level of education, training, work experience and information technology on the effectiveness of the accounting information system at PT. Sinar Niaga Sejahtera Jember. The type of research used is explanatory quantitatif reserch. The data used is primary data with data collection techniques namely questionnaires, observations, interviews and documentatioin. The number of respondents in this study were 40 people. Data analisys methods used are data instrument test, multiple linier regression, coefficient determination  (R²)  and hypotesis testing. The results of study indicate that personal skills and training have a partial effect on the effectivitveness of accounting information systems. While the leve of education, work experience and information technology do not partially influence the effectiveness of accounting information systems. Simultaneously personal ability, level of education, training, work experience and information technology affect the effectiveness of accounting systems.